2020
DOI: 10.1186/s41512-020-00089-w
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for the development and validation of a risk prediction model for stillbirths from 35 weeks gestation in Australia

Abstract: Background Despite advances in the care of women and their babies in the past century, an estimated 1.7 million babies are born still each year throughout the world. A robust method to estimate a pregnant woman’s individualized risk of late-pregnancy stillbirth is needed to inform decision-making around the timing of birth to reduce the risk of stillbirth from 35 weeks of gestation in Australia, a high-resource setting. Methods This is a protocol f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…In the UK, the stillbirth rate was largely unchanged from 2000 to 2015, and, in 2017, the rate was one of the highest in Europe, at 4.2 stillbirths/1000 births [3][4][5] . Prediction and individualization of risk remain key priorities for stillbirth research 6,7 , because accurate identification of women at high risk of stillbirth can guide decisions on the need for closer surveillance and timing of delivery in order to prevent fetal death. A recent review that identified existing prediction models for stillbirth reported that none had been validated externally 8 .…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, the stillbirth rate was largely unchanged from 2000 to 2015, and, in 2017, the rate was one of the highest in Europe, at 4.2 stillbirths/1000 births [3][4][5] . Prediction and individualization of risk remain key priorities for stillbirth research 6,7 , because accurate identification of women at high risk of stillbirth can guide decisions on the need for closer surveillance and timing of delivery in order to prevent fetal death. A recent review that identified existing prediction models for stillbirth reported that none had been validated externally 8 .…”
Section: Introductionmentioning
confidence: 99%
“…ROC analysis assesses the model's ability to classify observations by plotting sensitivity versus 1-specificity (25). The area under the curve (AUC) values were categorized as follows: high accuracy (0.9 < AUC-ROC ≤1), moderate accuracy (0.7 < AUC-ROC ≤0.9), and low accuracy (0.5 < AUC-ROC ≤0.7) (26). Calibration plots were used to assess the relationship between predicted survival probability and observed survival (27).…”
Section: Nomogram Construction and Validationmentioning
confidence: 99%
“…Although the study successfully motivated further endeavour for the development of such models in India, several design and reporting limitations hamper both inference and application. I propose the following methodological considerations for future studies on the topic based on our team’s experience with one of the largest studies ( n > 5,500 stillbirths) on stillbirth prediction to date, published in Nature Scientific Reports [ 3 ]; externally validated studies on preterm birth [ 4 , 5 ]; and a recent registered protocol [ 6 ].…”
Section: Main Textmentioning
confidence: 99%